2011
DOI: 10.1016/j.sbspro.2011.04.017
|View full text |Cite
|
Sign up to set email alerts
|

The status of college students’ critical thinking disposition in humanities

Abstract: Dyadic adjustment can be handled as a state in which there is an overall feeling of happiness and satisfaction with marriage. Women have become so much more active in work life over the past years that the changes in the roles of women also affect the communication with their husbands and as a result their dyadic adjustment. On this basis, the aim of this study is to determine the moderator role of employment status of women in the relationship between critical thinking disposition and dyadic adjustment of mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…It is considered as “consistent internal motivation to engage problems and make decisions by using CT” ( Facione, 2000 , p. 65). The prerequisite for the development of CT is to create an effective context and background for disposition towards it ( Khandaghi et al., 2011 ). It is reported that the training framework for CT without enough dispositions would fail ( Khandaghi and Pakmehr, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is considered as “consistent internal motivation to engage problems and make decisions by using CT” ( Facione, 2000 , p. 65). The prerequisite for the development of CT is to create an effective context and background for disposition towards it ( Khandaghi et al., 2011 ). It is reported that the training framework for CT without enough dispositions would fail ( Khandaghi and Pakmehr, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Agreeing with this, critical thinking disposition did not significantly vary according to gender for language and Mathematics education students (Turan, Kolayis, Ulusoy, 2012) as well as for humanities fields undergraduates (Khandaghi, et al, 2011). Likewise for the master's level counseling students and master's level business students.…”
Section: Critical Thinking Disposition and Gendermentioning
confidence: 62%
“…Nevertheless, scores on one of the sub-scales, Truth-seeking, was below what the authors of the instrument would deem as a positive inclination. Other studies involving undergraduate students have found that those in the College of Humanities achieved optimal level of critical thinking disposition (Khandaghi, Pakmehr, & Amiri, 2011) while prospective science teachers have medium and low levels of critical thinking disposition (Demirhan & Köklükaya, (2014). Hence, the need for more studies in critical thinking disposition arises especially as some researchers argue that before critical thinking skills can be examined, a positive disposition to think critically must exist (Facione, Sanchez, & Facione, 1994;Thayer-Bacon, 1993).…”
Section: Critical Thinking Dispositionmentioning
confidence: 99%
“…Furthermore, the mean scores of the faculty members were compared based on these numbers. If the mean score of the professors reached 50%, their critical thinking would be considered moderate, and if the score reached 70%, their critical thinking would be considered optimal (20). Based on the calculated mean scores, strong, moderate, and weak tendencies could be determined, with the scores ≥ 136.95 considered strong, scores of 135.30 -110.51 considered moderate, and scores ≤ 108.90 considered weak (21).…”
Section: Methodsmentioning
confidence: 99%